THERMAL BARRIER COATING AMDRY 962 AND METCO 204 NS WITH PLASMA SPRAY METHOD FOR F16 AIRCRAFT EXHAUST NOZZLE APPLICATION - Nur Muhammad, Yasya
The exhaust nozzle acts as a propulsion generator to help the aircraft maintain speed and operate under aggressive environments at high temperatures of around 900 °C to 1100 °C with turbine engine operating hours of nearly 50,000 hours and repeated. The nozzle converts the potential energy from the high temperature, then the high-pressure gas flow out of the engine into kinetic energy by amplifying the gas flow to high speed in the exhaust nozzle area. To protect the material from these conditions, modification of the properties and strength of the material is carried out, especially on the surface of the material. This can be done by coating the surface using a thermal barrier coating (TBC) material. The TBC layer serves as thermal insulation for important components in the aero and gas turbine industry. Under the operating conditions of the exhaust nozzle above, the TBC layer can be delaminated and worn on the surface of the coating. Therefore, the coating process is important because it affects the strength of the TBC layer. In this study, the thermal barrier coating process was carried out using the plasma spray method. Plasma spray process parameters, namely feed rate, spraying distance, and post heat treatment were varied with the aim of obtaining optimal coating process parameters with the results of a TBC layer that has a strong layer of tensile bond, a low amount of porosity, and good erosion resistance. The tests carried out were layer morphology on the microstructure, SEM-EDS testing, and XRD. Hardness testing was carried out by cross-section using a microhardness machine with an indenter knoop. Erosion testing was carried out with an air jet erosion machine with a reduced sample mass output. The tensile bond test of the layer was carried out by the tensile bond strength test. Residual stresses in the coating were tested with an x-ray residual stress analyzer. The results of the test showed that the material with a feed rate of 6 lb/H and a spraying distance of 4 inches produced a layer with a small amount of porosity, high erosion resistance, high tensile bond strength, and lower residual stress. While the post heat treatment parameter gives the effect of increasing the percentage of porosity, lowering the hardness value, and increasing erosion resistance